The intention to turnover and its relationship with healthy work environment among nursing staff - Sara-Sadat H; Reza Negarandeh; Leila Janani; Esmaeil Mohammadnejad; Elham Ghasemi (Tehran University of Medical Sciences, 2018)
Background & Aim: Nurses play an important role in the health system and their turnover disrupts its performance. The aim of this study was to investigate intention to turnover and its relationship with healthy work environment among nursing staff. Methods & Materials: This cross-sectional study was conducted on 295 nursing staff from Imam Khomeini hospital complex in Tehran in 2016. Nurses were selected by the stratified random sampling with a proportional allocation, and completed a demographic data form, the Healthy Work Environment questionnaire and the Anticipated Turnover Scale (ATS). Data were analyzed by descriptive statistics, independent t-test, one-way ANOVA, Pearson/Spearman correlation coefficient and multiple linear regression tests using the SPSS software version 20. Results: The mean score for the intention to turnover was 36.21 (SD=4.38) ranged from 12 to 60. "Authentic leadership" and "skilled communication" domains obtained the highest (9.60±3) and lowest (8.97±2.74) scores respectively. There was poor correlation between the meaningful recognition domain and the anticipated turnover score (r=-0.135, P=0.024). In addition, the anticipated turnover score was significantly higher in male nurses than in female nurses (P=0.023). Conclusion: Although there was no relationship between anticipated turnover and healthy work environment in this study, considering the importance of nurses' recruitment and retention, there is a need to investigate the reasons for turnover, including characteristics of work environment, and take necessary measures.